Nonlinear association of 1,5-anhydroglucitol with the prevalence and severity of coronary artery disease in chinese patients undergoing coronary angiography - Yang, Ruiyue; Zhang, Wenduo; Wang, Xinyue; Wang, Siming; Zhou, Qi; Li, Hongxia; Mu, Hongna; Yu, Xue; Ji, Fusui; Dong, Jun; Chen, Wenxiang (Frontiers in Endocrinology, 2022)
Background: Postprandial hyperglycemia plays an important role in the pathogenesis of coronary artery disease (CAD). The aim of this study is to determine the associations of 1,5-Anhydroglucitol (1,5-AG), which reflects circulating glucose fluctuations, with the prevalence of CAD and CAD severity in coronary angiography defined Chinese patients. Methods: 2970 Chinese patients undergoing coronary angiography were enrolled. Baseline demographics and medical history data was recorded. Serum 1,5-AG levels and biochemical parameters were measured. Baseline characteristics were compared across 1,5-AG categories in diabetes (DM) and non-DM groups. Logistic regression analysis was performed to evaluate the associations of 1,5-AG with the prevalence and severity of CAD. Results: Lower 1,5-AG was significantly associated with higher Gensini scores in both DM and non-DM groups. Logistic regression analysis demonstrated that the associations of low 1,5-AG with the prevalence of CAD, elevated Gensini score and severe CAD robustly dose-response increased from undiagnosed DM with 1,5-AG ≥ 14µg /mL to DM with 1,5-AG < 14µg /mL even after adjusting for fasting blood glucose (FBG) or Hemoglobin A1c (HbA1c). The associations were more significant in persons with DM. Significant modification effect of DM on the relationship of 1,5-AG with elevated Gensini score was found. In addition, nonlinear relationship and threshold effects of 1,5-AG with CAD and severity were observed. Conclusion: Low 1,5-AG is significantly and independently associated with CAD and CAD severity in Chinese patients undergoing coronary angiography. Measurement of 1,5-AG is useful to differentiate subjects with extensive glucose fluctuations and high CAD risks, especially in DM patients. This study was registered in ClinicalTrials.gov (Identifier: NCT03072797, Dated March 7, 2017).